Shursuv and Shursuv Industrial Zone - Zhobborov Azam Mashrabovich; Tojiboeva Mahliyo Azamzhon kizi; Karimov Shoulug Zokirjon ugli (Research Parks Publishing LLC, 2021)
This booklet provides information about the town of Shursuv, one of the first industrial centers of Fergana region, its geographical location, climate, nature, minerals, industries, agriculture, population and economic development of the region